Muhammadiyah Was Born in Java and Raised in Minangkabau: History, Intellectualism, and the Modern Islamic Movement - Rifana Wahdi; Ali Amat; Ahmad Lidra; Ahmad Lahmi; Mursal Mursal (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
The article Muhammadiyah Was Born in Java and Raised in Minangkabau: History, Intellectualism, and the Modern Islamic Movement discusses the history of the birth of Muhammadiyah as a Modern Islamic movement in Indonesia, focusing on Java as the birthplace and Minangkabau as the place of growth and development and the size of this organization. Muhammadiyah was founded by KH Ahmad Dahlan as a quick response to the condition of Muslims who were trapped in the practice of Tahayul, Bid'ah and Churafat (TBC), the weakness of the education system, the fading of religious thought and resistance to Dutch colonialism. Through qualitative analysis and a historical approach to various library sources, this research targets the causes of the birth, process of spread, acceptance and growth of Muhammadiyah in Minangkabau. The results of this research show that the social and intellectual conditions of Minangkabau society are very much in line with the spirit of reform or tajdid promoted by Muhammadiyah, such as the Islamic scientific tradition, the culture of going abroad for men, as well as the Minang philosophy, adat basandi syarak, syarak basandi kitabullah. This Minangkabau climate has supported the development of Muhammadiyah in Minangkabau, not only as an Islamic organization but also as an intellectual force, impacting educational reform, Islamic thought, and progressive Islam. Consequently, the phrase